Who are the Bitcoin investors? Evidence from indirect cryptocurrency investments - Dominique Marcel Lammer; Tobin Hanspal; Andreas Hackethal (Leibniz Institute for Financial Research SAFE, 2020)
Cryptocurrencies have received growing attention from individuals, the media, and regulators. However, little is known about the investors whom these financial instruments attract. Using administrative data, we describe the investment behavior of individuals who invest in cryptocurrencies with structured retail products. We find that cryptocurrency investors are active traders, prone to investment biases, and hold risky portfolios. In line with attention effects and anticipatory utility, we find that the average cryptocurrency investor substantially increases log-in and trading activity after his or her first cryptocurrency purchase. Our results document which investors are more likely to adopt new financial products and help inform regulators about investors' vulnerability to cryptocurrency investments.
urn:nbn:de:hebis:30:3-534536
Keywords: G50; G40; D14; G11; G15; G02; 330; Bitcoin; Cryptocurrencies; Structured retail products; Retail investors; Household finance; Investor behavior